Emerging Antibodies in Cancer Therapy. Issue 1 (7th December 2022) - Sun, Yaping; Xu, Jian
Abstract : Since the first monoclonal antibody, Orthoclone OKT3, was approved in 1986 for the treatment of acute allograft rejection in renal transplant recipients, the number of antibody‐based therapies has increased remarkably, with more than 130 monoclonal antibodies being currently available. In particular, due to their robust binding affinity and high specificity, various monoclonal antibodies have achieved success as complementary antitumor drugs. Moreover, therapeutic potency can be improved by engineering Y‐shaped binding sites of the antibodies to simultaneously recognize two distinct antigens; such molecules are called bispecific antibodies and function as a bridge, with one site binding to a tumor‐specific antigen and the other to immune cells to activate host immune responses. In addition, the development of trispecific antibodies has led to further enhancement of therapeutic specificity and effects. Indeed, a variety of structurally engineered antibodies have proven effective in tumor therapy. This article provides insights into the clinical translation of emerging antibody constructs, firstly describing conventional T cell‐redirecting bispecific antibodies and subsequently discussing the application of bispecific and trispecific antibody constructs based on innate immune cell recruitment. Finally, bispecific antibodies against mutant p53 and KRAS that have been actively studied in cancer treatment are introduced. Abstract : Improving the function of the immune system is one of the effective strategies against malignant tumors. In particular, therapies involving the activation and redirection of innate immune cells, including natural killer cells and macrophages, have received considerable attention in recent years. Emerging bispecific and trispecific antibodies developed on this basis are also considered to have great potential in cancer therapy.